Composite phase change materials for thermal energy storage: From molecular modelling based formulation to innovative manufacture. (February 2019) - Li, Chuan; Li, Qi; Zhao, Yanqi; Cong, Lin; Jiang, Zhu; Li, Yongliang; Ding, Yulong
Abstract: Thermal energy storage (TES) has a crucial role to play in conserving and efficiently utilising energy, dealing with mismatch between demand and supply, and enhancing the performance and reliability of our current energy systems. A competitive TES technology requires a number of scientific and technological challenges to be addressed including TES materials, TES components and devices, and integration of TES devices with energy networks and associated dynamic optimization. This paper concerns mainly about TES materials challenges with a specific focus on using shape stable composite phase change materials (CPCMs) for medium and high temperature application. The paper first briefly reviews the state-of-the-art development of materials research for thermal energy storage. The focus is then on CPCMs for medium to high temperatures applications, covering materials screening, formulation based on molecular modelling validated at a different length scale through experiments, formulation based on chemical and physical compatibility, and manufacture of material modules via innovative use of conventional powder technology. The properties of the materials and materials modules are characterised and analysed with an aim to establish property-structure relationships. This includes a particularly interesting aspect of the motion of PCM and nanoscale objects with the PCMs for heat transfer enhancement during thermal cycling, which explains the mechanisms of the encapsulation of PCMs in the composite.